Bioremediation of Soil Contaminated with Diesel Using Inorganic Nitrogen Sources: Incorporating nth-Order Algorithm in the Evaluation of Process Kinetics. Issue 1 (2nd January 2018) - Onwosi, Chukwudi O.; Nwankwegu, Amechi S.; Enebechi, Charles K.; Odimba, Joyce N.; Nwuche, Charles O.; Igbokwe, Victor C.
ABSTRACT: In the present study, we investigated the effects of inorganic nitrogen sources—(NPK fertilizer, 15:15:15), (urea fertilizer, 46:0:0), (NH4 )2 SO4 as well as monitored natural attenuation on the bioremediation of diesel-polluted soil. At the end of the 6-week study, the highest degradation was recorded in soil amended with NPK fertilizer (95 ± 2.77%) while the least total petroleum hydrocarbon removal was observed in monitored natural attenuation (89 ± 2.91%). N th-order kinetics effectively described three of the treatments out of the four treatment plans. These include urea amendment ( r 2 = 0.9925, average relative error ( ARE ) = 1.45%, root mean square error ( RMSE ) = 0.038, kn = (3.57 ± 0.61) × 10 −2, n = 1.33), NPK fertilizer amendment ( r 2 = 0.9751, ARE = 3.241%, RMSE = 0.086, kn = (8.04 ± 0.23) × 10 −1, n = 0.74), and monitored natural attenuation ( r 2 = 0.9697, ARE = 2.77%, RMSE = 0.073, kn = (1.57 ± 0.50) × 10 −2, n = 1.16). The values of n from the n th-order kinetics parameter estimation indicated that all the treatments resulted in diesel degradation that followed a first-order kinetics path. Thus, the outcome of kinetic modeling showed that n th-order can be used as validating tool when many kinetic orders are under consideration. The phytotoxicity assay with Zea mays showed that the treatments plans resulted in germination indices of 17–55%.